2019
DOI: 10.1016/j.neuroscience.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Subgranular Zone FosB Expression Is Critical for Neurogenesis and Learning

Abstract: Neural proliferation in the dentate gyrus (DG) is closely linked with learning and memory, but the transcriptional programming that drives adult proliferation remains incompletely understood. Our lab previously elucidated the critical role of the transcription factor ΔFosB in the dorsal hippocampus (dHPC) in learning and memory, and the FosB gene has been suggested to play a role in neuronal proliferation. However, the subregion-specific and potentially cell-autonomous role of dHPC ΔFosB in neurogenesis-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…This hypothesis, however, has been difficult to explore because of the lack of reagents to identify NtsR1 neurons to study their specific Nts-mediated signaling pathways. Recently established genetic models now permit site-specific modulation of NtsR1-expressing cells that may assist the field in defining the coupling of NtsR1 across different brain regions ( 1 , 98 , 124 , 125 ), and thus the mechanism by which Nts-NtsR1 signaling modulates physiology.…”
Section: Central Neurotensin Receptors and Weight Modulationmentioning
confidence: 99%
“…This hypothesis, however, has been difficult to explore because of the lack of reagents to identify NtsR1 neurons to study their specific Nts-mediated signaling pathways. Recently established genetic models now permit site-specific modulation of NtsR1-expressing cells that may assist the field in defining the coupling of NtsR1 across different brain regions ( 1 , 98 , 124 , 125 ), and thus the mechanism by which Nts-NtsR1 signaling modulates physiology.…”
Section: Central Neurotensin Receptors and Weight Modulationmentioning
confidence: 99%
“…Previous studies showed FosB-/- mice inhibited microglial activation and the production of pro-inflammatory cytokines to control neuropathic pain (14,15). The levels of FosB in the dorsal hippocampus play an important role in both learning and hippocampal neurogenesis (25). Only persistent heterotopic pain in mice led to elevated FosB expression in the amygdala and the central nucleus of the spinal cord, and FosB levels remained elevated in the basal lateral amygdala of mice, which resulted in significant pain relief and persistent behavioral effects (15).…”
Section: Discussionmentioning
confidence: 99%
“…ΔFosB has a well-established role in NAc in mediating stress susceptibility 13 15 and regulates synaptic and intrinsic properties of NAc medium spiny neurons 16 . It is also necessary in dorsal hippocampus (dHPC) for learning 17 , and regulates the excitability of dHPC CA1 neurons 18 as well as hippocampal neurogenesis 19 , 20 . ΔFosB is induced throughout HPC by stress and antidepressant treatment 13 , 21 23 , and vHPC CA3 ΔFosB is critical for the prophylactic effects of ketamine on stress responses 23 .…”
Section: Introductionmentioning
confidence: 99%